What Do You Do With a Voice Like That? : The Story of Extraordinary CongressWoman Barbara Jordan - Barton, Chris; Holmes, Ekua (New York, 2018)
"A picture book of lawyer, politician, and civil rights leader Barbara Jordan."--Provided by publisher.
Includes bibliographical references.
Keywords: Jordan, Barbara; 1936-1996; Juvenile literature; Jordan, Barbara; 1936-1996; Biography; United States; Congress; Congress; United States; Biography; African American women legislators; Legislators; Texas; Biography; African American women legislators; African American women legislators; United States; Biography; Legislators; Biography; Politics and government; Texas; Juvenile literature; 1951-